The Effect of Service Quality, Product Quality, and Price on Customer Loyalty (Case Study on Robusta Coffee Customers Kec. Kepahiang Kab. Kepahiang) - Ayu Puspita Sari; Eti Arini (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the effect simultaneously between Service Quality, Product Quality, and Price on Customer Loyalty in Robusta Coffee Shop, Kepahiang District, Kepahiang District. This study uses a research method using purposive sampling sample, data collection using research instruments, data analysis quantitatively. The population in this study were 95 customers at the Coffe Robusta shop, Kepahiang District, Kepahiang Regency. There are several data analysis techniques used in this research, including using instrument test, classical assumption test, respondent response analysis, multiple linear regression analysis, determinant coefficient, and hypothesis testing. From the results of the tests that have been done, it can be concluded that the variables of Service Quality (X1), Product Quality (X2) and Price (X3) have a partial or simultaneous effect on Customer Loyalty in the Robusta Coffee shop, Kepahiang District, Kepahiang District. From the results of multiple linear regression tests, the regression equation is obtained as follows: Y = 1.824 + 0.452 (X1) + 0.259 (X2) + 0.234 (X3).